UNCOVERING THE SCIENCE MULTILITERACY MODEL AND ITS RELATIONSHIP TO STUDENTS' CRITICAL THINKING SKILLS IN ELEMENTARY SCHOOL: - - Hasanah, Uswatun; -, Edwita; -, Imaningtyas; Januar, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to reveal the role of the multiliteracy model and its influence on critical thinking skills for fifth-grade elementary school students. This study is an experimental study with a research design used in this study, namely Pretest Posttest Control Group Design. The data analysis technique in this study is the T-test. The study results showed that based on the difference test with the independent samples test, it is known that the Sig. (2-tailed) value of 0.00 is smaller than 0.05, thus it can be concluded that there is a significant difference between the average critical thinking skills of students in the experimental class and the group of students in the control class. The results of this study can be a recommendation for elementary school teachers in improving the quality of learning including enhancing their students' critical reasoning.